The Implementation of Russian Federation’s Coercive Diplomacy towards Ukraine in the New Great Game Context over Gas Pipeline Dispute (2006 -2009) - Anak Agung Banyu Perwita; Nurhayati Pakpahan (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Unair, 2016)
The worsening of technical and safety condition of the pipeline infrastructure in Ukraine due to economic crisis following the end of the Cold War had driven Russia to provide compensation to Ukraine through applying subsidy on its gas price and paying the Ukrainian gas imports as long as Ukraine keep its promise to pay back the country’s debt until 2005. However, since Ukraine’s integration with the United States and its Western Allies by asking to become part of North Atlantic Treaty Organization and European Union state members, it refused to pay its high gas debts to Russia. This situation made Russia feels threatened towards its national security where there will be a possibility to the fall of Russian political influence in Ukraine. In 2006, Russia decided to implement its coercive diplomacy actions towards Ukraine through politicizing its gas sector.